A Review : Dietary Fiber Biochemical Inductions and Its Hypocholesterolemic Effects - Sri Rahajoe Asj'ari (Indonesian Association of Food Technologists, 2002)
Most people already know that dietary_ fiber can have detrimental or beneficial effects on health, primarily with regard to nutritional status. In this writing one of the beneficial effects of the consumption ofdietary fiber especially its hypocholesterolemic effect will be discussed. Many research papers have already showed regarding the connection between the biochemical induction of soluble fiber and the hypocholesterolemic effect of soluble fiber. In these investigations treatments were given to various kinds of experimental animals and to humans as experimental subjects. Kinds of foods were used as sources of fiber. The researchers were able to discover a variety of biochemical inductions that led to a hypocholesterolomic effect and were able to lower the cholesterol concentration in various kinds of lipoprotein fractions. Biochemical inductions discovered were, among others: fiber making food difficult to be digested, thereby inhibiting lipid absorption, decreasing cholesterol synthesis, increase of cholesterol excretion through the bile, decreasing of Apo B synthesis in the liver, decrease of the mRNA Apo B concentration of the liver, decrease in mRNA Apo A-I and mRNA Apo A-IV concentration in intestinal cells, decrease in HMG-CoA reductase activity and decrease in insulin secretion. Every soluble .fiber from specific sources of dietary fiber produced a certain biochemical induction and also hypocholesterolemic effect to a certain lipoprotein fraction. The concentration of total cholesterol and cholesterol in lipoproteins containing Apo B, and the LDL-C: HDL-C ratio are all lowered. Thus the patient is able to choose as a source offiber, the food of his or her preference appropriate to his or her kind of hypercholesterolemic disorder, with the goal of reduction of cholesterol concentration.